PENGARUH ETIKA PERILAKU PENJUAL TERHADAP LOYALITAS MELALUI KEPUASAN DAN KEPERCAYAAN PELANGGAN PADA DEALER MOBIL NISSAN BASUKI RAHMAT SURABAYA - WIHARTONO, JEFRRY (Universitas Katolik Widya Mandala Surabaya, 2013)
In this era of globalization of business competition has made many companies to compete to capture and maintain market share. In this case one of the sectors included in the corporate world is the automotive sector. Especially in the field of automobile sales, the seller should be able to find a variety of appropriate strategies to achieve competitive advantage, in the hope of maintaining the market and win the competition. Marketing theory suggests that the key to an organization's success depends on the ability to dynamically interact, and also services, particularly ethical behavior will affect the seller's satisfaction and trust that will lead to customer loyalty This study aims to determine the relationship between ethical behavior seller relationship on customer loyalty through customer satisfaction and confidence in the nissan car dealer Surabaya Basuki Rahmat. The object of research is in the community and outside Surabaya Surabaya who've never made a purchase in dealler nissan car Nissan Surabaya Basuki Rahmat. The samples are 104 respondents and using analytical SEM (Structural Equation Modeling) program through the Student LISREL 8.70. The findings in the can is variable sellers ethical behavior no significant effect on loyalty, but significant effect on customer satisfaction and trust as well as a significant mediating effect on loyalty, satisfaction and confidence while having a significant impact on loyalty.